A Comparison of Death Domain-Associated Protein 6 in Different Endometrial Carcinomas Histotypes. Issue 14 (July 2019) - Jin, Cao; Hacking, Sean; Komforti, Miglena K; Nasim, Mansoor
Background: Death domain-associated protein 6 (DAXX) is involved in regulating apoptosis via subcellular localization. The presence of DAXX point mutations correlates well with loss of nuclear expression on immunohistochemistry (IHC). In this study, we sought to determine (1) whether DAXX expression pattern is the same across different uterine carcinoma subtypes, and (2) which uterine carcinomas show loss of nuclear DAXX IHC. Design: We studied 65 uterine carcinomas of the following histologic types: 30 endometrioid (12 FIGO [The International Federation of Gynecology and Obstetrics] grade 1, 12 FIGO grade 2, and 6 FIGO grade 3), 8 serous, 14 clear cell, and 13 undifferentiated/dedifferentiated type (UEC/DDEC). Nuclear DAXX IHC was assessed in each tumor and was graded semi-quantitatively as follows: 0% to 50%, 50% to 75%, and greater than 75% of lesional cells react. Results: A total of 61% (25/41) of high-grade carcinomas (FIGO grade 3, serous, clear cell, and UEC/DDEC]) showed retained DAXX nuclear staining in >75% of lesional cells, compared with only 4.2% (1/24) of the low-grade carcinomas (FIGO grades 1 and 2) ( P = .0001), where DAXX expression was cytoplasmic. In addition, in the 11 DDEC cases, all the differentiated components showed loss of nuclear DAXX compared with the undifferentiated components which retained nuclear DAXX expression. Conclusions: We demonstrate that loss of nuclear DAXX is present in low-grade endometrial carcinomas and the differentiated components in UEC/DDEC, but not in high-grade ones, suggesting DAXX's role in tumor progression and its potential as a therapeutic target in high-grade endometrial carcinomas.